2009
DOI: 10.21608/jhiph.2009.20738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Occupational Combined Exposure to Organic Solvents and Noise in Printing Industry

Abstract: In working environments where organic solvents such as toluene, Benzyene, xylene, styrene, and trichloroethylene are used, noise is also common. Thus, ototoxicity of an organic solvent has a probable interaction with noise under such environments. The present study aimed to evaluate the occupational combined exposure to organic solvents and noise exposures in printing industry, where several departments were selected as raw material storage, white process, color process, ultraviolet process, and design area as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Seventeen studies of offset printeries, in which individual VOC concentrations were reported, were identified (Batterman et al 2002;Caselli et al 2009;Ćurčić et al 2013;El-Said 2009;Gegic and Savic 2013;Gioda and de Aquino Neto 2002;Godoi et al 2009;Hautamäki et al 2006;Lee et al 2009;Leung, Liu, and Chan 2005;Mansouri et al 2015;Rodriguez and Gibbins 2007;Sancini et al 2014;Svendsen and Rognes 2000;Thanacharoenchanaphas et al 2007aThanacharoenchanaphas et al , 2007bYu et al 2004). Just one used evacuated canister sampling methodology (Leung, Liu, and Chan 2005).…”
Section: Voc Concentrations From Previous Studiesmentioning
confidence: 99%
“…Seventeen studies of offset printeries, in which individual VOC concentrations were reported, were identified (Batterman et al 2002;Caselli et al 2009;Ćurčić et al 2013;El-Said 2009;Gegic and Savic 2013;Gioda and de Aquino Neto 2002;Godoi et al 2009;Hautamäki et al 2006;Lee et al 2009;Leung, Liu, and Chan 2005;Mansouri et al 2015;Rodriguez and Gibbins 2007;Sancini et al 2014;Svendsen and Rognes 2000;Thanacharoenchanaphas et al 2007aThanacharoenchanaphas et al , 2007bYu et al 2004). Just one used evacuated canister sampling methodology (Leung, Liu, and Chan 2005).…”
Section: Voc Concentrations From Previous Studiesmentioning
confidence: 99%